2009
DOI: 10.2471/blt.08.058370
|View full text |Cite
|
Sign up to set email alerts
|

Meeting oxygen needs in Africa: an options analysis from the Gambia

Abstract: Objective To compare oxygen supply options for health facilities in the Gambia and develop a decision-making algorithm for choosing oxygen delivery systems in Africa and the rest of the developing world. Methods Oxygen cylinders and concentrators were compared in terms of functionality and cost. Interviews with key informants using locally developed and adapted WHO instruments, operational assessments, cost-modelling and cost measurements were undertaken to determine whether oxygen cylinders or concentrators w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 18 publications
1
63
0
Order By: Relevance
“…These are the need for models that will operate reliably in challenging conditions and the need for a constant power supply to run them. 11 This article deals with the first of these, surveying the models of concentrator currently available and assessing their suitability for use in the developing world, tropical countries in particular. This work is part of a broader project aimed at improving the availability of oxygen treatment in The Gambia, a sub-Saharan African country, and learning lessons that may be applied more broadly in similar settings.…”
mentioning
confidence: 99%
“…These are the need for models that will operate reliably in challenging conditions and the need for a constant power supply to run them. 11 This article deals with the first of these, surveying the models of concentrator currently available and assessing their suitability for use in the developing world, tropical countries in particular. This work is part of a broader project aimed at improving the availability of oxygen treatment in The Gambia, a sub-Saharan African country, and learning lessons that may be applied more broadly in similar settings.…”
mentioning
confidence: 99%
“…Studies consistently reported the importance of procuring oxygen concentrators that were proven to work in hot and humid conditions. This was based on observations of maintenance problems and premature equipment failure when projects provided untested concentrators or used a variety of concentrator types (Gray et al) 28 , 36 , 46 , 51 , 53 …”
Section: Resultsmentioning
confidence: 99%
“…We assumed that no extra operations would be carried out as a result of introducing oximetry and that no extra clinical staff time would be required. We included supplementary oxygen 9 resulting from an increase in the incidence of detected hypoxia 10 when oximetry is used.…”
Section: Methodsmentioning
confidence: 99%